Molecular Dynamics of Kapitza Resistance at the Solid-Liquid Interface of Nanofluidic Channels - Kio, Michael Tamuno Elekima (Cranfield University, 2014)
This project sought to study the heat transfer and Kapitza resistance of fluids across interfaces, nanopores and nanochannels with varying sti.ness constants, mass and energy intermolecular in- teraction strength of wall and fluid particles. An Einstein-Maxwell molecular dynamics thermal wall model is developed. The developed modeling approach is shown to provide dual energy and momentum transport exchange across solid-liquid interfaces and nanofluidic channels. Cont/d.